Pengaruh Konsentrasi Pelarut NaOH dan Waktu Aging pada Pembuatan Silika Gel dari Fly Ash Batu Bara - Fatimah; Turmuzi, Muhammad; Syam, Zanni Latifah; Yunita, Trisna Putri (Jurnal Teknik Kimia USU, 2023)
Fly ash has the potential to be used as a raw material in the production of silica gel. This study aims to characterize fly ash and silica gel, determine the effect of NaOH concentration and aging time on the manufacture of silica gel, and determine the trapping power of silica gel. In this research, the production of silica gel begins with the washing of fly ash using HCl. Next, NaOH is added with varying concentrations of 1.5 N, 2.5 N, 3.5 N, and 4.5 N. The formed Na2SiO3 is then mixed with H2SO4 of 3 N concentration, with aging times of 12 hours, 15 hours, and 18 hours. The highest yield of silica gel is 49.61% at a NaOH concentration of 4.5 N and an aging time of 15 hours. The highest water vapor adsorption capacity of the silica gel is 883.00 mg/g at a NaOH concentration of 3.5 N and an aging time of 15 hours. SEM-EDX characterization results indicate a diverse morphology and size for both fly ash and silica gel. The SiO2 content in fly ash is 41.64%, while in silica gel, it is 41.42%. FTIR characterization of fly ash and silica gel reveals the presence of functional groups such as silanol (Si-O), siloxane (Si-O-Si), and hydroxyl (Si-OH) which are active sites in silica gel.